Musical-educational Cycle of Lectures in a Museum as a Method of Developing Musical-esthetic Culture of an Individual (International Journal of Psychosocial Rehabilitation, 2020)
The research objective is to theoretically and practically substantiate the use of a musical-educational cycle of lectures in a museum as a method of developing the musical-esthetic culture of an individual. The leading research method is systemic analysis of the Russian and foreign literature. The polling method enabled to trace the dynamics of developing a musical-esthetic culture of an individual by means of musical-educational lectures. Theoretical analysis helped to elaborate the basic provisions and directions of the cycle of lectures and to organize them in the museums and galleries of Kazan. When considering the phenomenon of musical-esthetic culture, its main components were defined, and the potential of the museum space as an object of cultural-leisure establishment was revealed. As a result of implementing the musical-educational cycle of lectures in a museum during one and a half years, the musical-esthetic culture of its participants increased.